Re-Annexation of Indian Occupied Kashmir: Challenges and Options for Pakistan - Babar, Babar Aman (Journal of Public Policy Practitioners, 2023)
This paper intends to evaluate the Kashmir issue in the backdrop of the Indian actions of 5th August, 2019. Firstly, some basics of the State of Kashmir and the Kashmir issue have been narrated. Thereafter, an in-depth analysis of the Indian perfidy terming “annexation” as “accession”, elaborating the characteristics of the special status given to the occupied state, has been made. The actions of 5th August, 2019 whereby that status was completely revoked, “re-annexing” and dividing the state into two union territories, unilaterally, has been detailed. The impact of the “reannexation” has been framed, duly highlighting the plight of Kashmiris and lack of preparedness on the part of the State of Pakistan. However, some of the noteworthy initiatives by Pakistan after the Indian move have been underscored. Indian actions have resulted into various anticipated threats and opportunities for Pakistan which have been discussed in detail keeping in view the geo-strategic and internal and external socio-economic and political ground realities; some of which had compelled Modi to choose this particular point in time to realize the long-standing dream of BJP. It has been maintained that Pakistan needs to stick to its principled stand and concluded that Pakistan must take certain actions to minimize the threats and make best use of the opportunities coming its way. The recommendations have been made with a view to initiate a well-meaning effort in a systematic way through an institutionalized action plan to end the pain and suffering of the incarcerated people and to get Kashmir liberated from India in accordance with the wishes of the Kashmiris.